2020
DOI: 10.3389/fchem.2020.00213
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose Reinforced Thermoplastic Starch (TPS), Polylactic Acid (PLA), and Polybutylene Succinate (PBS) for Food Packaging Applications

Abstract: Synthetic plastics are severely detrimental to the environment because nonbiodegradable plastics do not degrade for hundreds of years. Nowadays, these plastics are very commonly used for food packaging. To overcome this problem, food packaging materials should be substituted with "green" or environmentally friendly materials, normally in the form of natural fiber reinforced biopolymer composites. Thermoplastic starch (TPS), polylactic acid (PLA) and polybutylene succinate (PBS) were chosen for the substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 199 publications
(111 citation statements)
references
References 68 publications
(68 reference statements)
1
96
0
Order By: Relevance
“…The biodegradable film retains food quality and is environmentally friendly [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Although several kinds of new polymers such as (polylactic acid (PLA), polyhydroxyalkanoates (PHA), polycaprolactone (PCL), and poly(ethylene adipate) (PEA) are industrially produced, agricultural based polymers are the most investigated by researchers, mainly polysaccharides [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Numerous researchers reported that reinforcement of essential oil into starch based packaging can increase their stability and retain their flavour and functional properties [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biodegradable film retains food quality and is environmentally friendly [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Although several kinds of new polymers such as (polylactic acid (PLA), polyhydroxyalkanoates (PHA), polycaprolactone (PCL), and poly(ethylene adipate) (PEA) are industrially produced, agricultural based polymers are the most investigated by researchers, mainly polysaccharides [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Numerous researchers reported that reinforcement of essential oil into starch based packaging can increase their stability and retain their flavour and functional properties [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The other advantages include low density, renewability, biodegradability, non-toxicity, good insulation property and low machine wear [ 13 , 21 ]. However, the common disadvantages of natural fibers are their hydrophilic nature, which leads to lower interfacial bonding and surface adhesion with the matrix, which has been reported by many researchers [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. This behavior leads to the deterioration of the properties of the biocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…As nanocellulose is used to reinforce synthesis polymer, it is also employed to reinforce biopolymer from natural resources to improve the properties of the natural polymer, such as polylactic acid (PLA), polyhydroxy acids (PHA), polyhydroxybutyrate (PHB), polybutylene succinate (PBS), and starch biopolymer [ 210 , 211 ]. Table 3 and Table 4 illustrate some examples of NCC and NFC reinforced biopolymer and show the effects of NCC as well as NFC fillers.…”
Section: Nanocellulose Reinforcing Biopolymer Compositementioning
confidence: 99%